Advances in physical organic chemistry. - Bethell, D. (Donald) (Advances in physical organic chemistry, 1995)
The objective of the serial is to present considered reviews on the quantitative study of organic compounds and their behavior--physical organic chemistry in its broadest sense--in a manner accessible to a general readership. This thirtieth volume contains four topics on diverse subjects.